Of being and doing in the Parque Bosques de San Carlos (Memorias Sifored - Encuentros Educación UAN, 2021)
Present the field trip as a methodological proposal within the didactic processes of Social Sciences for the teaching of Geography.
Keywords: field trip; methodological proposal; didactic; social sciences; teaching; Geography